The age of computational cardiology and future of long-term ablation target prediction for ventricular tachycardia - Moinuddin, Arsalan; Ali, Syed Yusuf; Goel, Ashish; Sethi, Yashendra; Patel, Neil; Kaka, Nirja; Satapathy, Prakasini; Sah, Ranjit; Barboza, Joshuan J.; Suhail, Mohammed K. (Frontiers in Cardiovascular Medicine, 2023)
Ventricular arrhythmias, particularly ventricular tachycardia, are ubiquitously linked to 300,000 deaths annually. However, the current interventional procedure—the cardiac ablation—predict only short-term responses to treatment as the heart constantly remodels itself post-arrhythmia. To assist in the design of computational methods which focuses on long-term arrhythmia prediction, this review postulates three interdependent prospectives. The main objective is to propose computational methods for predicting long-term heart response to interventions in ventricular tachycardia Following a general discussion on the importance of devising simulations predicting long-term heart response to interventions, each of the following is discussed: (i) application of “metabolic sink theory” to elucidate the “re-entry” mechanism of ventricular tachycardia; (ii) application of “growth laws” to explain “mechanical load” translation in ventricular tachycardia; (iii) derivation of partial differential equations (PDE) to establish a pipeline to predict long-term clinical outcomes in ventricular tachycardia.